KESESUAIAN LAHAN PERAIRAN PULAU KALEDUPA UNTUK KERAMBA JARING APUNG IKAN KERAPU - Hatim Albasri; Brian Szuster (Widyariset, 2010)
Capability analisis of waters off Kaledupa Island for Grouper Net Cage quaculture. This research was aimed to assess potential areas for sustainable grouper net cage mariculture within marine conservation areas using geographic information system (GIS) as the main tool for determining the suitability of the potential areas. The research took place on the southern part of Kaledupa Island and was conducted for three weeks in August, 2007. Data collection was performed in 31 sampling stations. There were 15 capability parameters measured in each sampling station. Data analysis was conducted using kriging-based interpolation analysis in ArcGIS 9.1 to describe the distribution of each parameter over the study area. The final capability map was the combination of all capability parameters into one single thematic map using Boolean operator. The result showed that there were 4,510.54 ha of capable area in the 8,581.99 ha of the study area. Therefore, it can arguably be concluded that the eastern coastline of Kaledupa Island is capable for supporting grouper net cage mariculutre.